Arthur and the forbidden city - Besson, Luc 1959- (HarperCollinsPublishers, 2005)
In order to find his grandfather's lost treasure and save the Minimoys, Arthur and his companions, including Princess Selinia, travel into the forbidden city ruled by Maltazard the Cursed